Production of hydrocarbon based solvent with low aromatic content using ASPEN Plus - Fardhyanti, Dewi Selvia; Prasetiawan, H.; Anwaruddin, Hisyam; Kusumaningtyas, R. D.; Mulya, S. T. S.; Findriyani, M. A. R.; Sasongko, N. A. (IOP Publishing Ltd., 2021)
The solvent is a liquid that can dissolve or extract specific materials. Solvents are needed for most chemical transformations to increase contact between reagents and catalysts. It also holds an important role in many studies, industrial chemical processes, coatings, and formulations of consumer products, however, most of the hydrocarbon-based solvents based still contain high aromatic content of benzene, toluene, and xylene which are carcinogenic chemicals. The separation of aromatic hydrocarbons from a mixture of C4-C10 aliphatic hydrocarbons is a complex process, due to its close boiling points and some combinations can form azeotropes. The general distillation process is not the right choice for the separation of aromatic hydrocarbons from a mixture of C4-C10 aliphatic hydrocarbons. Possible processes are liquid-liquid extraction, extractive distillation, and azeotropic distillation. In this study, extractive distillation using ASPEN Plus was performed to simulate the process. The crude feed composition used contains 77.13% aromatic compounds so that the separation technology used uses the extractive distillation process using sulfolane as a solvent. The variables used are the ratio of the crude feed to sulfolane (1:10, 1:15, 1:20), the number of stages (30, 40, 50), feed stage (15,20,25). Based on the simulation results, the best result was obtained by using the ratio of the crude feed to sulfolane of 1:10, with the number of stages 30, and the feed stage on the 25th stage.